Institutional values ​​and performance of the Iraqi political system (قضايا سياسية, 2024)
The establishment of the political system on a clear and specific institutional system is among the most prominent components of the democratic political system, as institutionalizing the political system makes its performance more capable of meeting the needs and requirements of individuals in society, due to the values that are generated from institutionalizing the system. Political, which is reflected in the thought and practice of the ruling political elites and members of society alike. Although more than two decades have passed since the democratic transition in Iraq, the Iraqi political system still suffers from the weakness and fragility of its democratic institutions, and this weakness and fragility has been consolidated in the performance of the political system and the system of values issued by it toward society. This, in turn, strengthened traditional values, weakened the rule of law, caused public policy lag, and replaced the system of mediation, nepotism, and political, financial, and administrative corruption with the system of competence, experience, and merit in managing the affairs of the Iraqi state and granting public positions.